2020
DOI: 10.3390/agronomy10091425
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Applications of Synthetic Auxins and Glufosinate for Escaped Palmer Amaranth Control

Abstract: Field and greenhouse studies were conducted to investigate the influence of sequence and timing of synthetic auxins and glufosinate on large Palmer amaranth (Amaranthus palmeri) control. Field studies were performed in Henry County, AL where treatments were applied to Palmer amaranth with average heights of 37 and 59 cm in 2018 and 2019, respectively. Sequential applications of 2,4-D/dicamba + glyphosate followed by (fb) glufosinate at labeled rates 3 or 7 days after initial treatment (DAIT) were used in addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 35 publications
2
5
0
Order By: Relevance
“…The pattern of A/Ci response differed between drift treatments and time of leaf development, indicating a high amount of photosynthetic plasticity which varied over herbicide exposure and time. These findings align with a recent study that showed dicamba exposure initially decreased photosynthesis by 22% in Palmer amaranth but improved over time (Browne et al 2020). Moreover, there was no evidence of maternal line nor population variation for morphological or physiological responses to herbicide drift, suggesting a high level of plasticity among all traits measured across individuals.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The pattern of A/Ci response differed between drift treatments and time of leaf development, indicating a high amount of photosynthetic plasticity which varied over herbicide exposure and time. These findings align with a recent study that showed dicamba exposure initially decreased photosynthesis by 22% in Palmer amaranth but improved over time (Browne et al 2020). Moreover, there was no evidence of maternal line nor population variation for morphological or physiological responses to herbicide drift, suggesting a high level of plasticity among all traits measured across individuals.…”
Section: Discussionsupporting
confidence: 92%
“…Dicamba is absorbed by plant leaves and mimics the deformative and growth-altering effects caused by overdoses of the natural plant auxin, indole-3-acetic acid (IAA) (Grossman 2010). Dicamba drift can cause a shift in plant and arthropod diversity (Egan et al 2014), delay the onset of flowering, reduce the number of flowers, and even reduce the amount of pollinator visits (Bohneblust et al 2016). However, we have very little information on how dicamba drift may impact plant-herbivore interactions.…”
Section: Introductionmentioning
confidence: 99%
“…The pattern of A – C i response differed between drift treatments and time of leaf development, indicating a high amount of photosynthetic plasticity, which varied over herbicide exposure and time. These findings align with a recent study that showed dicamba exposure initially decreased photosynthesis by 22% in Palmer amaranth , which then improved over time (Browne et al, 2020). Moreover, there was no evidence of maternal line nor population variation for morphological or physiological responses to herbicide drift, suggesting a high level of plasticity among all traits measured across individuals.…”
Section: Discussionsupporting
confidence: 92%
“…Research by Inman et al (2016) highlighted that the herbicide dicamba can also be used to control A. palmeri in some populations. Conversely, there have been several populations of A. palmeri that have evolved resistance to auxin herbicides such as 2,4‐D and dicamba (Browne et al, 2020; Heap, 2021; Kumar et al, 2019). In this regard, several steps should be taken to minimise herbicide resistance from evolving.…”
Section: Review Of the Research Into Control Techniquesmentioning
confidence: 99%